Cartografias para uma educação inventiva - Simon Junior, José Cavalhero (2017)
This research project has been moved by the desire to cartographize different processes of subjectification produced within the territory of education, as well as their effects on learning. In order for such an endeavor to take place, a path was chosen that comprised affects of a body predicated upon the institutionalized teachings of formal education, as well as its practices as an educator who wished to be in contact with inventive learning within teacher education for early childhood education. Such a design has enabled me to promote dialog with the philosophy of the Reggio Emilia Approach (Italy) and concepts created by Deleuze and Guattari, both of which have been employed so as to generate zones of confrontation between systems of institutionalized teaching – which at its core has consensual objectivity as a means for subjectification – and educational systems that revolve around inventive learning which in turn open up space for singularization processes, assemblages posited outside the institutionalized and the production of difference